2019
DOI: 10.1186/s12974-019-1449-9
|View full text |Cite|
|
Sign up to set email alerts
|

Expansion and activation of distinct central memory T lymphocyte subsets in complex regional pain syndrome

Abstract: BackgroundComplex regional pain syndrome (CRPS) is a debilitating condition where trauma to a limb results in devastating persistent pain that is disproportionate to the initial injury. The pathophysiology of CRPS remains unknown; however, accumulating evidence suggests it is an immunoneurological disorder, especially in light of evidence of auto-antibodies in ~ 30% of patients. Despite this, a systematic assessment of all circulating leukocyte populations in CRPS has never been performed.MethodsWe characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 92 publications
7
37
0
Order By: Relevance
“…CXCR3 expression on Bcells and a subset of double-negative T-cells was lower in patients than controls. The increase in central memory CD4+ T-cells and memory Tregs is consistent with the findings in a recent report that used mass cytometry to investigate blood immune subsets in complex regional pain syndrome, another condition in which inflammation persists long after the original injury (40).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…CXCR3 expression on Bcells and a subset of double-negative T-cells was lower in patients than controls. The increase in central memory CD4+ T-cells and memory Tregs is consistent with the findings in a recent report that used mass cytometry to investigate blood immune subsets in complex regional pain syndrome, another condition in which inflammation persists long after the original injury (40).…”
Section: Discussionsupporting
confidence: 90%
“…The relatively small sample size is also a key limitation of this study and further patient recruitment will be important to validate findings from this cohort. Nevertheless, this study is comparable to those of others that have also identified changes in PBMC profiles associated with sustained pathology (40) and provides new insight into the possible consequences of acute burn injury and an important basis for further research. Most importantly, whilst these experiments provide observations of changes in these cell populations, functional assays will be critical to understand the potential clinical consequences of the observed disparity between groups.…”
Section: Discussionsupporting
confidence: 84%
“…Second, both central and effector memory CD4 + T cells were shown to be significantly increased in chronic neuropathic pain patients with carpal tunnel syndrome (CTS) and complex regional pain syndrome (CRPS), as compared to healthy controls. The upregulation of memory CD4 + T cells (presumably Th cells) would be an indicator of the history of Th cell activation against a particular antigenic stimulus in CTS patients [73,74]. To our surprise, however, significant decrease of inflammatory Th1 or Th17 cells and increase of antiinflammatory Th2 or Treg cells were found in patients with chronic neuropathic pain as compared to healthy controls [75][76][77].…”
Section: Clinical Evidencesmentioning
confidence: 75%
“…The percentage of CD56 bright CD16 + cells were slightly increased in patients with broadly defined severe chronic pain, however, generalized NK cell cytotoxic activity and the frequency of the major NK cell subsets were not significantly different (Yoon et al, 2018). In a study of 14 patients with complex regional pain syndrome (CRPS) and 14 controls, Russo and colleagues used mass cytometry to identify an expansion of both CD4 + and CD8 + memory T lymphocytes in patients compared to controls (Russo et al, 2019). NK cells (defined as CD56 + CD19 − CD3 − ) were more than 50% elevated in CRPS patient blood but this did not reach significance.…”
Section: Immune Phenotyping After Injury or Painmentioning
confidence: 99%